Hubungan Pelayanan Phlebotomy Dengan Kepuasan Pasien dilaboratorium Klinik Rumah Sakit TNI AU Dr. Suhardi Hardjolukito Yogyakarta - Ratih Hardisari (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Patient satisfaction is an important quality indicator of hospital performance, especially for clinical laboratory services. At themoment, services given by medical laboratory technologist personnel in blood sampling section are not optimal. Air forceHospital Dr. Suhardi Hardjolukito Yogyakarta, a public hospital in Bantul, has clinical laboratory which serves patients fromthe members of Indonesian military, civil servants, general patient, patients with health insurance coverage and also patientswith national health insurance program (Jamkesmas). This study was aimed to know the correlation between phlebotomyservices and patient satisfaction in clinical laboratory of Air Force Hospital Dr. Suhardi Hardjolukito Yogyakarta. It was ast quantitative observational study with cross-sectional study. The data were collected from August 21 2016 until Septemberth 6 2016. The population of the study was taken from all outpatients of clinical laboratory in Air Force Hospital Dr. SuhardiHardjolukito Yogyakarta, by using simple random sampling. The data were collected by observing using check list,questionnaire, and document analysis with likert scale level measurement. The result of this study showed from 94respondents which were differentiated as five quality service dimensions of patient satisfaction: 88,3% for dimension ofreliability, 86,9% for dimension of quality assurance, 86,1% for dimension of empathy, 83,8% for dimension ofresponsiveness, 78,6% for dimensions of tangibles. Statistical analysis showed that there was a correlation betweenphlebotomy service and patient satisfaction (p < 0,1).